(untitled) (The Journal of Psychology and Sociology, 2019)
Higher education is becoming an integral stage in the life cycle of modern Kazakhstani youth, as education plays an important role in shaping the competitiveness of the young specialist. In the period of independence, the market of educational services of Kazakhstan is not only institutionalized, but also have been impacted by significant quantitative and qualitative reforms. Modern youth has a wide range of choices in the educational space, but nevertheless, according to the data of the Information and Analytical Center, only 12% of the total number of university graduates have done the job they were trained. Despite the expansion of opportunities affecting government regulation in providing the labor market with demanded specialists, the practice of successful employment is not only related to obtaining higher education, but is largely due to effective strategies of young people in choosing higher education. In this regard, the significance of the study of factors that are important for young people in choosing higher education is actualized. A sociological study of the strategies of young people in choosing higher education in all its versatility opens up new opportunities and prospects for their forecasting and regulation in accordance with the demands of the economy. This article presents the research findings of the complete process of choosing a higher education starting from educational plans to choosing university and specialty on the basis of the study among high school students and their parents. Key words: higher education, choice of profession, university prestige, educational plans, the level of education of parents, professional aspirations of school leavers, the value of higher education.